Serapan dan Efisiensi Penyerapan Hara N dan P Pada Pakcoy (Brassica rapa L. Ssp. Chinensis) Sistem Vertikultur di Lahan Kering - Wilda Lumban Tobing; Eduardus Yosef Neonbeni; Asep Ikhsan Gumelar; Maria Angelina Tuas; Rolinus Sabuna (Agrosains : Jurnal Penelitian Agronomi, 2022)
Pakcoy cultivation in dry land is still not optimal due to the growing environment that requires technology. Fertigation verticulture is used as an effort to increase pakcoy production in dry land. The purpose of this study was to determine the fertigation time, composition of planting media and the distance between planting holes and their interactions in increasing nutrient uptake and efficiency of N and P absorption for pakcoy plants on the vertical fertigation system. This research was carried out in the agricultural garden of the Main Seed Center of the North Central Timor Regency Agriculture Office from June to December 2021. The study used an experimental method with a Separate Plot Design with 3 plots where the main plot was the fertigation time which consisted of 3 levels, namely W1 (60 seconds). ), W2 (90 seconds), and W3 (120 seconds). The main subplot is the composition of the growing media which consists of 4 levels, namely: M1 (Soil: Sand (1:1)); M2 (Soil: Biochar (1:1)); M3 (Soil: Biochar (1:1)); and M4 (Soil: Sand: Biochar (1:1:1)). The subplots are the spacing of the planting holes consisting of 3 levels, namely: J1 (15 cm); J2 (20 cm); and J3 (25 cm). There were 36 treatments which were repeated 4 (four) times in order to obtain a total of 144 treatments. Data analysis used a comparative test using the Duncan Multiple Range Test method at 5% level. The results showed that the fertigation time of 120 seconds (W3) and the composition of the growing media: biochar (1:1) (M2) and their interactions increased the N and P uptake of pakcoy plants grown in a verticulture system on dry land by treatment. The fermentation time of 120 seconds (W3) and the composition of the growing media: biochar (1:1) (M2) also increased the efficiency of N and P nutrient absorption.